Selective and noncovalent targeting of RAS mutants for inhibition and degradation - Kai Wen Teng; Steven T. Tsai; Takamitsu Hattori; Carmine Fedele; Akiko Koide; Chao Yang; Xuben Hou; Yingkai Zhang; Benjamin G. Neel; John P. O’Bryan; Shohei Koide (Nature Communications, 2021)
Most oncogenic RAS mutants remain undruggable. Here, the authors developed monobodies that selectively recognize the active state of KRAS(G12V) and KRAS(G12C) and demonstrated their utility in inhibiting RAS functions through inhibition and degradation.